Comparison analysis on typical historic cultural districts with AI machine learning technology – Taking Portuguese and Macao districts as examples - Jiang Shan; Zheng Liang; Chen Yile; Zheng Jianyi (Lodz University of Technology Press, 2023)
With the rapid development of technology, artificial intelligence has gone into every field, and its development has been further expanded with machine learning as the core technology. How does this help urban analysis and urban form research? This study aims to introduce a new method for analysing and comparing urban morphological layouts using machine learning technology and to explore the possibility and potential of combining urban morphology analysis with machine learning technology. In this exploratory study, several typical Portuguese cities with historical and cultural characteristics are used as learning samples for comparison. Through the combination of urban morphology theory and machine learning, the urban morphological samples are clipped out from the Portuguese city maps, then morphological features are extracted from the samples, establishing training labels as typical Portuguese urban fabric, lastly compared the result with the typical urban areas of Macao using the YOLOv4 object detection algorithm. Through the research, it is found that Macao in the early stage is more morphologically similar to the city of Evora due to their same privilege; after the early 20th century, influence by contemporary Portuguese engineers and urban development strategy, Macao's urban morphology shows a higher degree of similarity to that of Lisbon.
Keywords: urban morphology; machine learning; urban fabric; comparison study; Macao; morfologia miast; uczenie maszynowe; tkanka miejska; badanie porównawcze